Self‐Monitoring and the Metatraits. Issue 3 (13th February 2015) - Wilmot, Michael P.; DeYoung, Colin G.; Stillwell, David; Kosinski, Michal
Abstract: Prior attempts at locating self‐monitoring within general taxonomies of personality traits have largely proved unsuccessful. However, past research has typically neglected (a) the bidimensionality of the Self‐Monitoring Scale and (b) the hierarchical nature of personality. The objective of this study was to test hypotheses that the two self‐monitoring factors are located at the level of the metatraits. Using data from two large multi‐informant samples, one community (Sample 1: N = 552, M age = 51.26, 61% female; N Peers = 1, 551, M age = 48.61, 37% female) and one online (Sample 2: N = 3, 726, M age = 24.89, 59% female; N Peers = 17, 868, M age = 26.23, 64% female), confirmatory factor analysis was used to test the hypotheses. Results confirmed hypotheses that acquisitive self‐monitoring would have a strong positive relation to metatrait Plasticity, whereas protective self‐monitoring would have a moderate negative relation to metatrait Stability. In both samples, constraining the correlation between acquisitive self‐monitoring and Plasticity to unity did not alter model fit indices, indicating that the two putatively distinct constructs are identical. Findings have wide‐ranging implications, including integration of the construct of self‐monitoring into the mainstream of personality research, as the latter moves toward the development of broad explanatory theories.